Combined chemotherapy and intra-arterial chemotherapy of retinoblastoma - Saerom Choi; Jung Woo Han; Hyosun Kim; Beom Sik Kim; Dong Joon Kim; Sung Chul Lee; Chuhl Joo Lyu (Korean Pediatric Society, 2013)
PurposeRetinoblastoma (RB) is the most common primary malignant intraocular tumor in children. Although systemic chemotherapy has been the primary treatment, intra-arterial chemotherapy (IAC) represents a new treatment option. Here, we performed alternate systemic chemotherapy and IAC and retrospectively reviewed the efficacy and safety of this approach.MethodsPatients diagnosed with intraocular RB between January 2000 and December 2011 at Severance Children's Hospital, Yonsei University, were reviewed. Before February 2010, the primary treatment for RB was chemotherapy (non-IAC/CTX). Since February 2010, the primary treatment for RB has been IAC (IAC/CTX). External beam radiotherapy or high-dose chemotherapy were used as "last resort" treatments just prior to enucleation at the time of progression or recurrence during primary treatment. Enucleation-free survival (EFS) and progression-free survival were assessed.ResultsWe examined 19 patients (median age, 11.9 months; range, 1.4 to 75.6 months) with a sum of 25 eyes, of which, 60.0% were at advanced Reese Ellsworth (RE) stages. The enucleation rate was 33.3% at early RE stages and 81.8% at advanced RE stages (P=0.028). At 36 months, EFS was significantly higher in the IAC/CTX group than in the non-IAC/CTX group (100% vs. 40.0%, P=0.016). All 5 patients treated with IAC achieved eye preservation, although most patients were at advanced RE stages (IV-V).ConclusionDespite the limitation of a small sample size, our work shows that an alternative combined approach using IAC and CTX may be safe and effective for eye preservation in advanced RB.